Characterization of the RNA-Binding Protein TcSgn1 in Trypanosoma cruzi - Camila Oliveira; André P. Gerber; Samuel Goldenberg; Lysangela R. Alves (Microorganisms, 2021)
RNA-binding proteins (RBPs) participate in several steps of post-transcriptional regulation of gene expression, such as splicing, messenger RNA transport, mRNA localization, and translation. Gene-expression regulation in trypanosomatids occurs primarily at the post-transcriptional level, and RBPs play important roles in the process. Here, we characterized the RBP TcSgn1, which contains one RNA recognition motif (RRM). TcSgn1 is a close ortholog of yeast Saccharomyces cerevisiae protein ScSgn1, which plays a role in translational regulation in the cytoplasm. We found that TcSgn1 in Trypanosoma cruzi is localized in the nucleus in exponentially growing epimastigotes. By performing immunoprecipitation assays of TcSgn1, we identified hundreds of mRNAs associated with the protein, a significant fraction of them coding for nucleic acids binding, transcription, and endocytosis proteins. In addition, we show that TcSgn1 is capable of interacting directly with the poly(A) tail of the mRNAs. The study of parasites under nutritional stress showed that TcSgn1 was localized in cytoplasmic granules in addition to localizing in the nucleus. Similar to ScSgn1, we observed that TcSgn1 also interacts with the PABP1 protein, suggesting that this protein may play a role in regulating gene expression in T. cruzi. Taken together, our results show that RNA-binding protein TcSgn1 is part of ribonucleoprotein complexes associated with nuclear functions, stress response, and RNA metabolism.